PENGARUH JUMLAH UANG BEREDAR DAN NILAI TUKAR RUPIAH (KURS) TERHADAP TINGKAT INFLASI DI INDONESIA PERIODE TAHUN 2017-2024 - Nuralifah, Eva Amalia; Pardistya, Irvan Yoga; Megawati, Liya (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: This study aims to analyze the influence of the money supply and the rupiah exchange rate on the inflation rate in Indonesia during the 2017-2024 period. This study is motivated by inflation fluctuations influenced by various macroeconomic factors, including monetary policy, money circulation dynamics, and exchange rate changes.Methods: The research method is quantitative, using multiple linear regression analysis. The data used include the inflation rate, the money supply, and the rupiah exchange rate..Results: The results of the descriptive analysis show that the money supply and the exchange rate experienced an increasing trend with fluctuations throughout the observation period. Partial tests indicate that the money supply has no significant effect on inflation. Similarly, the rupiah exchange rate also shows no significant effect on the inflation rate. Simultaneous tests conclude that neither variables significantly affect inflation.Conclusion and suggestion: These findings indicate that inflation in Indonesia is more influenced by other factors such as fiscal policy, domestic demand, and global commodity prices. Therefore, coordination of fiscal and monetary policies is necessary to maintain economic stability. Keywords: Exchange Rate, Inflation, Money Supply